Sonographic appearance of cysticercosis of the masseter muscle: A case report - Hemant Sawhney; Sanjeev Laller; Anju Anu Jose; Mamta Malik (Wolters Kluwer Medknow Publications, 2019)
Cysticercosis is an infection with the larval (cysticercus) stage of Taenia solium. The larvae form cysts commonly in brain, meninges, and eyes, which together constitute 86% of cases with remainder located in the muscles, heart, lungs, and peritoneum. Cases in the maxillofacial region, including tongue and cheek muscles are rare. We report a rare case of cysticercosis involving right masseter muscle presenting as a facial swelling, diagnosed on the basis of fine-needle aspiration cytology and high-resolution ultrasonography and managed conservatively.